Land suitability analysis using Geographic Information System (GIS) for sustainable land development in Jeli, Kelantan, Malaysia - Amal Najihah Muhamad Nor; Muhamad Azahar Abas; Jawagar Arumugam; Mohamad Pirdaus Yusoh; Normah Abdul Latip (Malaysia Institute of Planners, 2024)
Three (3) satellite images (2004, 2014, and 2022) were processed and analysed using a Geographic Information System (GIS) to obtain the land use types. The land suitability parameters were chosen based on population density and landscape factors such as slope, land use, elevation, and distance from rivers. The weights of each evaluation factor were determined using Analytical Hierarchical Analysis (AHP). Additionally, weighted overlay analysis, available in ArcGIS 10.8 software, was used to integrate all the parameters. This study found that Jeli’s build-up area increased from 1.9% in 2004 to 24.5% in 2022. The suitability map for Jeli’s land development has been reclassified into three (3) highly suitable categories (42.43%), moderately suitable (53.32%), and highly not suitable (4.25%). The area of land suitability for land use increases along with the population density. The findings of this study will help policymakers develop better strategic urban expansion policies.